Implementation of the Independent Curriculum in Indonesian Language Learning Based on Local Wisdom through P5 Project : - Umayah, Urip (Utamax : Journal of Ultimate Research and Trends in Education, 2024)
The uniqueness of this study lies in its exploration of the Merdeka Curriculum's Project for Strengthening the Pancasila Student Profile (P5) and its integration of local wisdom in Indonesian language learning. This research addresses the gap in understanding how this curriculum shift impacts character education by focusing on practical implementation in elementary schools. The primary objectives are to investigate the methods schools use to incorporate local wisdom into Indonesian language learning and to identify obstacles encountered in this process. Using purposive sampling, data were collected through surveys and interviews with educators and students, and analyzed using descriptive statistical methods and qualitative coding. Findings from three schools indicate successful implementation of the P5 project, which not only enhances students' competencies but also fosters their development as Pancasila students, reflecting values such as mutual cooperation, global diversity, and creativity. Despite encountering challenges such as limited resources and varying levels of understanding among educators, the study highlights effective practices and the crucial role of community and parental involvement. The implications of this study suggest that integrating local cultural values into the curriculum can significantly enrich character education, ensuring students are better equipped to navigate and contribute positively to a globalized world while preserving their national identity. This research underscores the importance of continuous support and collaboration among educators, parents, and policymakers to optimize the benefits of curriculum innovations like the P5 project.